Analisa Kesadaran Hukum Atas Kepemilikan Merek Terdaftar Pada Umkm Binaan PT. Sarana Infotekno Mitra Solusi Di Daerah Istimewa Yogyakarta - Rahayu, Giovani Bajeng (JIPRO: Journal of Intellectual Property, 2021)
The high number of MSME actors is a positive thing related to Indonesian economic movement. MSMEs today are one of the pulse economic movement in Indonesia, and is one of the major sources of income for country. Technology that is developing rapidly makes the MSME market too develop. This research will more specifically examine the perpetrators of SMEs craftsmen batik built by PT. Sarana Infotekno Solution Partner. Small and Medium Enterprises, batik craftsmen has great potential in Yogyakarta. As one of the cities of batik, SMEs Batik in Yogyakarta has a fairly large market potential, in addition to assets in the form of: design and brand is also a big enough potential. Awareness of perpetrator MSMEs on Brand Ownership Rights are still considered low. Research purposes This is to find out the legal awareness of batik craftsmen in fostered MSMEs PT. Sarana Infotekno Mitra Solusi about the importance of registration awareness brands, as well as to find out the legal protection for brands that have not been registered with the MSMEs fostered by PT. Sarana Infotekno Solution Partner. This research is an empirical legal research, and the data in This research was obtained by using semi-structured interviews with There are 6 correspondents consisting of five MSME actors, as well as one director of PT. Sarana Infotekno Solution Partner. From the results of the interview, it was obtained that the awareness data of MSME actors was still low very low. Brand is seen as a means of promotion and a requirement for business legality. MSME actors still do not understand that there are various kinds of risks which may occur if the mark is misused by another party. On the other hand, SMEs actors also do not consider that the brand they own is a valuable asset for the business owned.